Improved anticancer effects of albumin-bound paclitaxel nanoparticle via augmentation of EPR effect and albumin-protein interactions using S-nitrosated human serum albumin dimer - Kinoshita, R.; Ishima, Y.; Chuang, Victor; Nakamura, H.; Fang, J.; Watanabe, H.; Shimizu, T.; Okuhira, K.; Ishida, T.; Maeda, H.; Otagiri, M.; Maruyama, T. (Elsevier Ltd, 2017)
© 2017 Elsevier Ltd In the latest trend of anticancer chemotherapy research, there were many macromolecular anticancer drugs developed based on enhanced permeability and retention (EPR) effect, such as albumin bound paclitaxel nanoparticle (nab- PTX, also called Abraxane ® ). However, cancers with low vascular permeability posed a challenge for these EPR based therapeutic systems. Augmenting the intrinsic EPR effect with an intrinsic vascular modulator such as nitric oxide (NO) could be a promising strategy. S-nitrosated human serum albumin dimer (SNO-HSA Dimer) shown promising activity previously was evaluated for the synergistic effect when used as a pretreatment agent in nab-PTX therapy against various tumor models. In the high vascular permeability C26 murine colon cancer subcutaneous inoculation model, SNO-HSA Dimer enhanced tumor selectivity of nab-PTX, and attenuated myelosuppression. SNO-HSA Dimer also augmented the tumor growth inhibition of nab-PTX in low vascular permeability B16 murine melanoma subcutaneous inoculation model. Furthermore, nab-PTX therapy combined with SNO-HSA Dimer showed higher antitumor activity and improved survival rate of SUIT2 human pancreatic cancer orthotopic model. In conclusion, SNO-HSA Dimer could enhance the therapeutic effect of nab-PTX even in low vascular permeability or intractable pancreatic cancers. The possible underlying mechanisms of action of SNO-HSA Dimer were discussed.